Degradation of superparamagnetic iron oxide nanoparticle-induced ferritin by lysosomal cathepsins and related immune response. (May 2012) - Laskar, Amit; Ghosh, Moumita; Khattak, Sikander Iqbal; Li, Wei; Yuan, Xi-Ming
Aim: To examine the physiological impact of superparamagnetic iron oxide nanoparticles (SPIONs) on cell function and its interaction with oxysterol laden cells.Materials & methods: Intracellular iron was determined by Prussian blue staining. Cellular ferritin, cathepsin L and ferroportin were analyzed by flow cytometry and fluorescence microscopy. Cytokine secretion was determined by ELISA and immunoblotting.Results: In U937 and THP 1 cells, we did not detect any loss of cell viability on SPION loading. Desferrioxamine prevents induction of both ferritin and cathepsin L by SPIONs. Inhibition of lysosomal cathepsins upregulates both endogenous- and SPION-induced ferritin. SPION loading induces membranous ferroportin and incites secretion of ferritin, TNF-α and IL-10. 7β-hydroxycholesterol exposure reduces SPION uptake by cells.Conclusion: SPION loading results in upregulation of lysosomal cathepsin, membranous ferroportin and ferritin degradation, which is associated with secretion of both pro- and anti-inflammatory cytokines. A reduced SPION uptake by oxysterol-laden cells may lead to a compromised MRI with elevated cathepsins and ferritin. Original submitted 8 March 2011; Revised submitted 6 July 2011; Online publication date 13 April 2012